KONSEP KERAMAHTAMAHAN DAN WACANA MODERASI BERAGAMA DALAM KONTEKS SULAWESI UTARA - Tifany Fergie Tombokan; Nency Heydemans; David Simanjuntak; Dennis Palar (Institut Agama Kristen Negeri Manado, 2024)
Religious moderation is one of the priority programs of the Ministry of Religion of the Republic of Indonesia. This discourse was developed and socialized in such a way as to address various cases of intolerance that lead to crimes in the name of religion. Within the scope of Christianity, religious moderation which contains the values of openness and acceptance is found in one of the ancient traditions of Christianity, namely hospitality. In this article, the author will examine the concept of hospitality according to Christine Pohl's writings and its implications in the discourse on Religious Moderation, especially in North Sulawesi. The research method used is a qualitative method based on literature study.